Exploring Obstacles and Solutions in the Implementation of Problem-Based Learning in Online Education: Eksplorasi Hambatan dan Solusi dalam Penerapan Problem-Based Learning pada Pembelajaran Daring - Hermawan, Candra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
This study aims to identify and analyze the main obstacles and solutions in the implementation of Problem-Based Learning (PBL) in online learning. The importance of this research lies in its effort to enhance the effectiveness of PBL in an online environment, which faces unique challenges related to interaction, collaboration, and the limitations of technology and student motivation. The research method used is a qualitative approach with a case study design, involving eight biology teachers experienced in online PBL. Data were collected through in-depth interviews and analyzed using thematic analysis to identify key themes regarding the obstacles and solutions encountered. The results show technical obstacles, such as unstable internet connections and limited devices, which affect student participation. Other challenges include difficulties in collaboration and interaction, limited understanding of the material due to the lack of direct guidance, and decreased student motivation. Teachers addressed these challenges by implementing various strategies, such as using breakout rooms, assigning roles within groups, providing structured guidance, and segmenting tasks to increase student engagement and understanding. The conclusion of this study is that although there are significant challenges in implementing online PBL, the use of adaptive strategies can improve the effectiveness of learning. This study highlights the importance of technological support and methodological adjustments to overcome barriers in online PBL. The limitations of this study include the inability to objectively measure student engagement and the difficulty in equalizing technological access across the research area. Further research is recommended to develop a hybrid approach to learning to enhance face-to-face interaction.